Comparison between NICE and NICE-1 Algorithms In Virtual network systems (International Journal of Engineering and Computer Science, 2014)
Cloud computing has gained adequate attention in the recent times due to its ease and customizability. However, cloud security has been a never ending issue faced by the users. Attackers take hold of the cloud system to gain access to third party information. Network Intrusion Detection and Countermeasure selection (NICE) is one particular technique that adopts multipath distributed vulnerability detection with the help of OpenFlow network programming API’s. On the other hand,   NICE-1 adopts a similar architecture but makes use of an efficient host-based IDS involving firewall that manages any number of attackers. The latter is compatible and cost effective when compared to the former.